FAST DATA ACQUISITION SYSTEM - Florin GROFU (Fiabilitate şi Durabilitate)
The paper proposes the realization of a two-channel data acquisition system that can be used for the acquisition and analysis of signals taken from industrial processes or for performing experiments in the laboratory. The proposed system is relatively simple and with a low cost of realization that can be used in the situation where it is necessary to analyze some analog signals that require acquisition speeds of up to 100,000 Samples / second.